Research on Overconfidence in Decision-Making for the Capacity Recovery of Damaged Power Systems - Xing Bao (Discrete Dynamics in Nature and Society)
This paper studies the influence of two types of overconfident behavior, overestimation and overprecision, on decision of capacity recovery when power system’s critical capacity is seriously damaged. A newsvendor model is used to prove that increasing regulatory punishment for electricity shortage and providing subsidy for capacity recovery are conducive measures to calibrate insufficient service level caused by an overconfident manager. The research also finds that the manager’s overprecision behavior both negatively and positively influences the decision of capacity recovery, and a calibration method could motivate manager to recover more capacity by tuning up the ratio of punishment and subsidy. However, the effectiveness of the calibration mentioned above is inevitably weakened due to the less capacity recovery given by an overestimated manager. This research also indicates that the manager should pay close attention to the random disturbance whose distribution peak is left skewed, and correspondingly more capacity recovery should be given to improve the service level of power system during the disruption.